EARLY VERSUS DELAYED ORAL INTAKE IN PATIENTS AFTER CESAREAN SECTION UNDER REGIONAL ANESTHESIA - Laiqa Hassan (Army Medical College Rawalpindi, 2021)
Objective: To compare the outcome in early versus delayed oral intake in patients after cesarean section under regional anesthesia.